Calcitonin Gene–Related Peptide Monoclonal Antibody Versus Botulinum Toxin for the Preventive Treatment of Chronic Migraine: Evidence From Indirect Treatment Comparison - Lu, Jiajie; Zhang, Quanquan; Guo, Xiaoning; Liu, Wei; Xu, Chunyang; Hu, Xiaowei; Ni, Jianqiang; Lu, Haifeng; Zhao, Hongru (Frontiers in Pharmacology, 2021)
Background: The previously approved botulinum toxin and nowadays promising calcitonin gene-related peptide (CGRP) monoclonal antibody have shown efficacy for preventing chronic migraine (CM). However, there is no direct evidence for their relative effectiveness and safety. In this paper, we conducted an indirect treatment comparison to compare the efficacy and safety of CGRP monoclonal antibody with botulinum toxin for the preventive treatment of chronic migraine. Methods: Up to August 31, 2020, we systematically searched PubMed, Embase and Cochrane Library Central Register of Controlled Trials (Central). Weighted mean difference (WMD) and Relative risk (RR) were used to evaluate clinical outcomes. Indirect treatment comparison (ITC) software was used to conduct indirect treatment comparison. Results: Ten studies were pooled with 6325 patients in our meta-analysis. Both botulinum toxin and CGRP monoclonal antibody demonstrated favorable efficacy in the change of migraine days, headache days and HIT-6 score, 50% migraine responder rate compared with placebo. In indirect treatment comparison, CGRP monoclonal antibody was superior to botulinum toxin in the frequency of acute analgesics intake (WMD=-1.31, 95%CI: -3.394 to 0.774, P=0.02113), the rate of treatment-related adverse events (AEs) (RR=0.664, 95%CI:0.469 to 0.939, P=0.04047) and the rate of treatment-related serious adverse events (RR=0.505,95%CI:0.005 to 46.98, P<0.001). Conclusion: For chronic migraine patients, CGRP monoclonal antibody was slightly better than botulinum toxin in terms of efficacy and safety. In the future, head-to-head trials would be better to evaluate the efficacy and safety between different medications in the prevention of chronic migraine.